A novel three-dimensional elliptical vibration cutting device based on the freedom and constraint topologies theory. (February 2019) - Lin, Sheng; Kong, Xi; Wang, Chun; Zhai, Yun; Yang, Liang
Aiming at the issue of the lack of the design theory for the three-dimensional elliptical vibration cutting device, a compliant mechanism with two rotations and one translation is synthesized based on the theory of freedom and constraint topologies. And a three-dimensional elliptical vibration cutting device is proposed on the basis of the compliant mechanism. The relationship between the critical speed and the length of the tool bar is analyzed. Simulation is conducted to analyze the influence of parameters on the output ellipse. Experiments are conducted to verify the validity of the elliptical vibration cutting device. The relationship between the roughness and the cutting speed is obtained. Experiments with different driving frequencies are conducted without the change of other parameters. Results show that the proposed compliant mechanism is feasible for the elliptical vibration cutting device. Compared with the common cutting, the new elliptical vibration cutting device has a better performance in the processing effect. This provides an important reference for design of the elliptical vibration cutting device.